Leiomyoma vaginal and uterine in female dog: Case report - de Lima, Gustavo; Terrabuio Andreussi, Paulo Antonio (Pubvet, 2019)
Vaginal and vulvar tumors comprise the most frequent neoplasms of the tubular reproductive tract in bitches. Leiomyoma is a benign neoplasm of smooth muscle mesenchymal origin, often diagnosed in the genital tract, especially in the vagina and uterus. Hormonal dysregulation in non-castrated bitches may favor the appearance of this neoplasia. They are macroscopically characterized as slow, well encapsulated and poorly vascularized mass. This report describes two cases, one vaginal and one uterine, attended at the Veterinary Hospital of the Faculty of Veterinary Medicine and Animal Science of the Federal University of Mato Grosso do Sul.